Effect of solvent : solid ratio, solvent, temperature, time and method on extraction on total phenolic compound from propolis (Trigona Thoracica) - Hew, Chan Phang (2016)
Propolis is a resinous substance that is collected by bees from different plant sources. Propolis has been attracting the attention of researchers because it has several biological functions, such as antioxidant and antimicrobial effects, both conferred by phenolic compounds. The aim of this study was to identify a suitable solvent, solid to solvent ratio, temperature and method for extraction of propolis. Maceration method was conducted by using ethanol and water with solid to solvent ratio of 1:10 and 1:20, respectively to identify the most effective solvent and its composition. Next, maceration method with specific solvent and ratio was conducted at 25°C and 50°C to identify the most effective temperature. The ultrasound extraction was conducted with duty cycle of 10% and 20% to identify the most effective duty cycle. Then maceration method was further compared with ultrasound extraction method at specific temperature. The total polyphenol content of propolis extract was analysed by Folin-Ciocalteu method. In conclusion, ultrasound assisted extraction with ethanol (1:10) at 50°C is the most effective way to obtain the highest total phenolic content (53.96 mg GAE/g ) from extracts. Additionally, the ultrasound should be set with 20% duty cycle with the extraction time of 150 minutes.